Risk of hepatotoxicity with trastuzumab emtansine in breast cancer patients: a systematic review and meta-analysis. (April 2020) - Cobert, Amani M.; Helms, Catherine; Larck, Chris; Moore, Donald C.
Background: Trastuzumab emtansine (T-DM1) is an anti-HER2 antibody-drug conjugate indicated for the treatment of HER2-positive breast cancer. One of the most severe adverse events reported with T-DM1 is hepatotoxicity. The objective of our meta-analysis is to investigate the risk of hepatic adverse events in patients with breast cancer receiving T-DM1 compared with controls. Methods: We conducted a systematic review and meta-analysis of randomized clinical trials (RCTs) comparing T-DM1 with a control treatment in patients with HER2-positive breast cancer. Phase II/III RCTs with available event number or event rate of hepatic toxicity with an assessable sample size were included. Relative risk (RR) and corresponding 95% confidence intervals (CI) for all grade and high-grade (grade 3/4) aspartate aminotransferase (AST) and alanine aminotransferase (ALT) elevations were calculated. Results: Seven RCTs were deemed eligible and were included in the meta-analysis. The RR for all-grade AST and ALT elevations were 3.24 (95% CI 2.16–4.86; p < 0.00001) and 2.90 (95% CI 1.98–4.23; p < 0.00001), respectively. The RR for high-grade AST and ALT elevations were 2.73 (95% CI 1.07–6.93; p = 0.03) and 2.17 (95% CI 1.34–3.50; p = 0.002), respectively. Conclusions: Our meta-analysis demonstrates that T-DM1-based therapy is associated with an increased risk of AST and ALT elevations.